PKM PENGEMBANGAN INDUSTRI TENUN LURIK MELALUI MODEL PEMASARAN BERBASIS WEB DI CAWAS KABUPATEN KLATEN - Y. Anni Aryani; Doddy Setiawan; Evi Gantyowati; Irwan Trinugroho (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2021)
This activity will be carried at Mlese Cawas Klaten, Central Java. This area has potential that has been passed down from generation to generation to produce traditional striated fabrics and processed products. The people living around the area are mostly weavers and weaving workers. The village has the potential to develop lurik weaving skills. The main problems that exist for the craftsmen include management problems, especially marketing problems, production processes that are not optimal and have not carried out efficiency. This service activity will be carried out using several approaches, including conducting training in management and skills, training on web-based marketing methods for craftsmen and applying skir technology for efficiency of the production process.